Trauma-Related Altered States of Consciousness (TRASC) and Functional Impairment I: Prospective Study in Acutely Traumatized Persons. Issue 5 (20th October 2015) - Frewen, Paul; Hegadoren, Kathy; Coupland, Nick J.; Rowe, Brian H.; Neufeld, Richard W. J.; Lanius, Ruth
Abstract : A theoretical framework referred to as a 4-D model has been described for classifying posttraumatic stress symptoms into those potentially occurring within normal waking consciousness (NWC) versus those thought to intrinsically exemplify dissociative experiences, specifically, trauma-related altered states of consciousness (TRASC). As a further test of this theoretical distinction, this prospective study evaluated whether TRASC and NWC forms of distress incrementally and prospectively predicted functional impairment at 6 and 12 weeks following presentation at hospital emergency departments in the acute aftermath of traumatic events in 180 persons. Establishing the clinical significance of both TRASC and NWC-distress symptoms, we found that 6-week markers of TRASC and NWC-distress independently predicted 12-week self-reported levels of social and occupational impairment. We also observed broad support for various predictions of the 4-D model except that, in contrast with hypotheses, childhood trauma history was generally more strongly correlated with symptoms of NWC-distress than with TRASC. Future research directions are discussed.